2023
DOI: 10.3389/fmicb.2023.1163261
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus increases Prostaglandin E2 secretion in cow neutrophils by activating TLR2, TLR4, and NLRP3 inflammasome signaling pathways

Abstract: IntroductionIn clinical settings, dairy cows are often attacked by pathogenic bacteria after delivery, especially Staphylococcus aureus (S. aureus). Neutrophils have long been regarded as essential for host defense against S. aureus. Prostaglandin E2 (PGE2) can additionally be used as an inflammatory mediator in pathological conditions to promote the repair of inflammatory injuries. However, whether S. aureus can promote the accumulation of PGE2 after the infection of neutrophils in cows and its mechanism rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Even Katalin et al reported that m 6 A modifications suppress the ability of RNA to stimulate TLR3, TLR7, and TLR8, 38 they did not uncover the m 6 A-regulated expression level of TLR2, and our findings fill this knowledge gap. In fact, TLR2 is regulated by various mechanisms like infection and gut microbes, [39][40][41] and we have just discovered that m 6 A might be a regulatory mechanism during the TM infection process. Previous studies have shown that YTHDC2 primarily regulates RNA degradation through m 6 A modification.…”
Section: Discussionmentioning
confidence: 99%
“…Even Katalin et al reported that m 6 A modifications suppress the ability of RNA to stimulate TLR3, TLR7, and TLR8, 38 they did not uncover the m 6 A-regulated expression level of TLR2, and our findings fill this knowledge gap. In fact, TLR2 is regulated by various mechanisms like infection and gut microbes, [39][40][41] and we have just discovered that m 6 A might be a regulatory mechanism during the TM infection process. Previous studies have shown that YTHDC2 primarily regulates RNA degradation through m 6 A modification.…”
Section: Discussionmentioning
confidence: 99%
“…S. aureus has been reported to increase secretion of cytokines in bovine neutrophils. In dairy cow infected with wild-type S. aureus (SA113) and a lipoprotein-deficient strain of S. aureus (Δlgt), Δlgt was less effective than SA113 in inducing the production of IL-1β, IL-6, IL-8, IL-10, and PGE 2 within neutrophils [ 14 ]. In our study, a significant negative correlation ( P <0.05) was found between whey PGE 2 concentrations and LS on day 1 in the T group but not in the C group.…”
Section: Discussionmentioning
confidence: 99%
“…Investigating apoptosis at different time points could provide additional insights [ 24 ]. Although exposure to TLR ligands did not trigger apoptosis in bovine PMNs [ 25 ], their involvement in inflammasome activation and subsequent silent cell death through pyroptosis cannot be ruled out [ 19 ]. Investigating other cell death pathways, like necrosis, NETosis, and pyroptosis, could be informative as bovine neutrophils might employ alternative mechanisms against minor pathogens [ 15 , 20 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unraveling how bovine neutrophils recognize “minor players” like NASM and LAB, especially S. chromogenes , holds the key to understanding udder immunity dynamics. Upon pathogen recognition, bovine neutrophils wage war with classical tactics (phagocytosis, ROS, RNI, AMPs, granule enzymes) [ 17 ], and subtle strategies (NETs, inflammatory mediators) for comprehensive udder defense unfold [ 15 , 18 , 19 , 20 , 21 ]. Adding another layer to their defense, neutrophils undergo programmed death (apoptosis) to limit NASM and LAB infections and resolve inflammation, revealing the intricate interplay between host and pathogen.…”
Section: Introductionmentioning
confidence: 99%